2008
DOI: 10.1109/t-dei.2008.4446734
|View full text |Cite
|
Sign up to set email alerts
|

DC conduction and electrical breakdown of MgO/LDPE nanocomposite

Abstract: To understand basic electric properties of nano-sized magnesium oxide (MgO) / low-density polyethylene (LDPE) nanocomposite under DC voltage application, the volume resistivity, the space charge distribution and the breakdown strength were investigated. By the addition of nanosized MgO filler, both the DC breakdown strength and the volume resistivity of LDPE increased. At the average DC electric field of about 85 kV/mm and more, a positive packet space charge was observed in LDPE without MgO nano-filler, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
103
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(119 citation statements)
references
References 13 publications
(12 reference statements)
11
103
0
2
Order By: Relevance
“…Lots of research works on nanodielectric BD properties under ac or dc voltage have been done so far [15][16][53][54][55][56][57][58][59][60][61]. Many useful experimental data are obtained.…”
Section: Breakdown Properties Of Nanodielectricsmentioning
confidence: 99%
“…Lots of research works on nanodielectric BD properties under ac or dc voltage have been done so far [15][16][53][54][55][56][57][58][59][60][61]. Many useful experimental data are obtained.…”
Section: Breakdown Properties Of Nanodielectricsmentioning
confidence: 99%
“…For low loading concentration, the charge suppression can be observed clearly by the pulsed electroacoustic method (PEA), while charge transport behavior becomes more complicated for high loading concentration. 3 Literature reports and our own measurement results indicated that the conductivity properties in nanodielectrics show different changes for different loading concentrations, [3][4][5][6][7][8] as shown in Figure 1. The polymer matrixs are LDPE (Low density polyethylene), LLDPE (Linear low density polyethylene), and PI (Polyimide), respectively.…”
mentioning
confidence: 99%
“…It has also been found that the related electrical performance, surface flashover, and breakdown deteriorate for nanodielectrics with high concentrations. 3,4,8,9 At present, the exact mechanisms of charge transport in nanodielectrics are not detailed, and the observed experiment phenomenon of charge conduction in nanodielectrics with high loading concentrations has never been fully explained.…”
mentioning
confidence: 99%
“…It has been shown in several instances that with the incorporation of nanoparticles, the space charge accumulation in polymers is substantially reduced [23]. As examples, nanometer-size fillers of silica (SiO 2 ) [24] and magnesium oxide (MgO) [25] incorporated into low-density polyethylene (LDPE) have been shown to be effective in suppressing space charge. The mechanisms behind those improvements are not completely clear at present [26], neither is the fate of the material integrity in time.…”
Section: Challenges Regarding Materials For Hvdc Cablesmentioning
confidence: 99%